2007
DOI: 10.1093/ageing/afm049
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of NSAID gastropathy in elderly patients. An observational study in general practice and nursing homes

Abstract: Patients in nursing homes had more risk factors for NSAID gastropathy than patients in old people's homes or outpatients (>65 years). Although in nursing homes co-prescription of prophylaxis during NSAID use is more common, in general the Dutch guidelines on adequate NSAID use are still not fully implemented at this moment. The results also showed that pantoprazole was effective in diminishing gastrointestinal complaints, as well as preventing symptomatic NSAID gastropathy. Moreover, pantoprazole showed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Our findings are consistent with other Dutch studies reporting under‐prescription of preventive strategies in patients who would benefit from appropriate protection at a range of 43–87% 33, 36–41 . Consistently low rates of prescription of preventive strategies have also been reported in studies from other countries 28, 42–45 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with other Dutch studies reporting under‐prescription of preventive strategies in patients who would benefit from appropriate protection at a range of 43–87% 33, 36–41 . Consistently low rates of prescription of preventive strategies have also been reported in studies from other countries 28, 42–45 .…”
Section: Discussionsupporting
confidence: 92%
“…37 and 38 The other 2 consisted of a referral center population 35 and a national sample from participating general practices. 36 The forest plot in Figure 3 shows little overlap in the CIs, indicating high heterogeneity (I 2 = 97%). The study investigating low-dose aspirin 35 was included in the analysis because aspirin has also been shown to be associated with GI bleeding (mitigated by use of PPIs), 58 and excluding this study did not reduce the heterogeneity (I 2 = 98%).…”
Section: Efficacymentioning
confidence: 98%
“…60 Likewise, the funnel plot ( Supplementary Figure 1) is not considered reliable with fewer than 10 studies. 61 Potential sources of heterogeneity include differences in the choice of outcome measure (self-reported GI complaints, 36 GI hospitalization rate, 37 and 38 hospitalization with upper GI event, 39 and 54 ulcers found on endoscopy, 35 or serious ulcer complications 55 and 56 ), the definitions of drug exposure and co-prescription, and differences in prescribing behavior leading to greater or lesser differences in baseline risk between treated and untreated patients. Three of these 5 37, 38 and 39 plus an additional 2 studies 54 and 55 reported efficacy of PPIs after adjustment for various risk factors (Table 2) but did not report outcome measures that could be combined.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a survey of 615 elderly patients in an outpatient or old age/nursing home setting for the coadministration of an NSAID with a prophylactic product to protect against gastrointestinal side effects, 65.3%, 76.2%, and 42.6% failed to receive necessary prophylaxis in the outpatient, old age, and nursing home settings, respectively [42], even though treatment for such side effects are documented in well-established guidelines put forth by the American Geriatric Society [43]. Another safeguard is the task of proper documentation of medical history.…”
Section: Physician Barriers In Nsaid Pain Managementmentioning
confidence: 99%